Tuning of direct bandgap of Rb2ScTlX6 (X = Cl, Br, I) double perovskites through halide ion substitution for solar cell devices - H.H. Hegazy; Ghulam M. Mustafa; Ali Nawaz; N.A. Noor; A. Dahshan; Imed Boukhris (Journal of Materials Research and Technology, 2022)
Optoelectronic devices designed with double perovskites are potentially emerging nowadays because of their interesting properties, such as simple and stable crystal structure. Our study theoretically explored the optoelectronic, mechanical, and thermoelectric characteristics of Rb2ScTlX6 (X = Cl, Br, I) based on the density functional theory of the Wein2k code. The thermodynamic and structural stability is determined based on the enthalpy of formation and tolerance factor. The character of the compositions has been checked that either they are ductile or brittle by the elastic constants which are used to measure Passion and Pugh's ratio. For the elaboration of band gaps, Tran-Blaha mBJ potential is used, and the measured values of energy bandgaps are 3.5, 3.0, and 2.4 eV for Rb2ScTlCl6, Rb2ScTlBr6, and Rb2ScTlI6, respectively, using TB-mBJ plus spin-orbital coupling (SOC). These compositions are potentially used in solar cell devices like heterojunction solar cells because their electronic characteristics are controllable. In the energy range 0–12 eV, the compositions under consideration exhibit a single-peaked response, while the replacement of anions from Cl to I caused a shift in optical structures towards lower energies. The significant value of the figure of merits 0.77–0.95 makes them suitable for thermoelectric device applications.